The role of insurance companies on economic development - Ayoker , Lam Bukeje (IJRDO - Journal of Social Science and Humanities Research, 2022)
This study is focuses on the role of insurance companies on economic development.  The aim of this research is to know the services that provided by insurance companies in South Sudan. The researcher collected data by using questionnaire and data analysis conducted using statistical package for social science (SPSS). Key finding: the study revealed that the insurance companies play vital role in economic development in South Sudan, most of insurance companies are generating revenue from premium, insurance industry plays great role in increasing GDP, payment of claims is one of most important things for insurance company, insurance companies  are financial institution, insurance companies in South Sudan are operating without insurance Act, in South Sudan insurance companies are operating without regulatory authority ,insurance increases employment in economy. Recommendations: The researcher recommends that  the legislative Assembly should pass an insurance bill for insurance companies operations, the government should establish the insurance regulatory authority for insurance industry in country, the insurance companies should have reinsurance arrangement with international reinsurance companies .the government should reduce taxes imposed on insurance companies, the insurance companies should aware public about importance of insurance, the insurance companies should pay the claims on time, government should provide insurance companies with hard currency for reinsurance.